School Principal Leadership In Growing Entrepreneurial Value In The Southwest Aceh Public Special School - Muhammad Sahuddin; Cheng Jinkuan; Verawati Verawati (Seutia Hukamaa Cendekia, 2023)
Education is an opportunity for citizens to gain knowledge. The government is committed that every child has the right to buy, especially children with special needs. Adequate education is given to respect and protects children with special needs without any discrimination in education. Educational services for students with special needs form responsible for the success of education. The condition of students with special needs, which are different from the characteristics of normal children, requires more handling and attention. Qualitative research with descriptive method. The research location is at the Southwest Aceh public special school. The sampel research of the principal, teachers and students of Southwest Aceh public Special school. Data collection techniques using the method of observation, interviews, and documentation studies. The research results on the role of school principals in fostering entrepreneurial values ​​in students by implementing the gigeh program, such as hydroponic skills, skills to make crispy kipang, catfish farming, mask making, and decoration. This gigeh program also fosters entrepreneurial value for children with special needs and encourages the establishment of a Pancasila student profile